A new species of Tozzita Kramer (Hemiptera: Cicadellidae: Neocoelidiinae) and first record of Tozzita ips Kramer from Brazil - Gonçalves, Clayton Correa; Marques-Costa, Ana Paula; Ale-Rocha, Rosaly (Zootaxa, 2013)
A new species of Tozzita Kramer, 1964, Tozzita bifida sp. nov., is described and illustrated. The new species can be dis-tinguished from the other species of the genus by the following characteristics: (1) forewing with commissural brown band; (2) pygofer with dentiform process on ventral margin and apex not spatulate; (3) subgenital plates with macrosetae at apex; (4) style with preapical lobe developed and produced posteriorly; (5) aedeagus symmetrical; (6) anal tube with bifid basal process. Tozzita ips Kramer, 1964 is firstly recorded from Brazil. Additionally, an updated genus description and an identification key to males of the species are provided. s yh0and it is contrasted with the described cases in Anillini. Typhlocharis scrofa n.sp. and T. tetramera n.sp. have club-shaped gono-coxites, reminiscent of the unguiform-like morphology observed in T. quadridentata (Coiffait, 1969), supporting the hy-pothesis of a transitional evolution of the shape of gonocoxites. The structure of the gula is studied within the genus and includes wide, narrow and diffuse morphologies. The implications of these features and data from the new species enable us to propose a reorganization of the systematics of the genus, creating and defining a new group of species, quadridentata group. An identification key for this species group is included. The new species provides more data on syntopic species and abundance rates, brief insights on the ecology of the genus.